Fair Trade and the Depersonalization of Ethics - Ballet, Jérôme (Journal of business ethics, 2010)
Fair Trade has changed considerably since its early days. In this article, we argue that these changes have led to a depersonalization of ethics, thus raising serious questions about the future of Fair Trade. In particular, the depersonalization of ethics which is seen to accompany the current changes has led to greater variety in the interpretations of Fair Trade. Hiding these divergences behind the labels is increasing the risk that the movement will lose its credibility.